Advances in Molten Slags, Fluxes, and Salts Proceedings of the 10th International Conference on Molten Slags, Fluxes, and Salts 2016 - Reddy, Ramana; Chaubal, Pinakin; Pistorius, P. Chris; Pal, Uday (The Minerals, Metals & Materials Series,, 2016)
This collection focuses on ferrous and non-ferrous metallurgy where ionic melts, slags, fluxes, or salts play important roles in industrial growth and economy worldwide. Technical topics included are: thermodynamic properties and phase diagrams and kinetics of slags, fluxes, and salts; physical properties of slags, fluxes, and salts; structural studies of slags; interfacial and process phenomena involving foaming, bubble formation, and drainage; slag recycling, refractory erosion/corrosion, and freeze linings; and recycling and utilization of metallurgical slags and models and their applications in process improvement and optimization. These topics are of interest to not only traditional ferrous and non-ferrous metal industrial processes but also new and upcoming technologies.